Reevaluation of Acromegalic Patients in Long-Term Remission according to Newly Proposed Consensus Criteria for Control of Disease. (21st December 2014) - Verrua, Elisa; Ferrante, Emanuele; Filopanti, Marcello; Malchiodi, Elena; Sala, Elisa; Giavoli, Claudia; Arosio, Maura; Lania, Andrea Gerardo; Ronchi, Cristina Lucia; Mantovani, Giovanna; Beck-Peccoz, Paolo; Spada, Anna
Abstract : Acromegaly guidelines updated in 2010 revisited criteria of disease control: if applied, it is likely that a percentage of patients previously considered as cured might present postglucose GH nadir levels not adequately suppressed, with potential implications on management. This study explored GH secretion, as well as hormonal, clinical, neuroradiological, metabolic, and comorbid profile in a cohort of 40 acromegalic patients considered cured on the basis of the previous guidelines after a mean follow-up period of 17.2 years from remission, in order to assess the impact of the current criteria. At the last follow-up visit, in the presence of normal IGF-I concentrations, postglucose GH nadir was over 0.4 μ g/L in 11 patients (Group A) and below 0.4 μ g/L in 29 patients (Group B); moreover, Group A showed higher basal GH levels than Group B, whereas a significant decline of both GH and postglucose GH nadir levels during the follow-up was observed in Group B only. No differences in other evaluated parameters were found. These results seem to suggest that acromegalic patients considered cured on the basis of previous guidelines do not need a more intensive monitoring than patients who met the current criteria of disease control, supporting instead that the cut-off of 0.4 mcg/L might be too low for the currently used GH assay.